2020
DOI: 10.3389/fmicb.2020.00296
|View full text |Cite
|
Sign up to set email alerts
|

Potential Antifungal Targets Based on Glucose Metabolism Pathways of Candida albicans

Abstract: In recent years, fungal infections have become a serious health problem. Candida albicans are considered as the fourth most common isolates associated with approximately 40% mortality in bloodstream infections among hospitalized patients. Due to various limitations of classical antifungals used currently, such as limited kinds of drugs, inevitable toxicities, and high price, there is an urgent need to explore new antifungal agents based on novel targets. Generally, nutrient metabolism is involved with fungal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…Glucose is an essential nutrient for the human body, serving as a primary fuel for energy production [ 1 ]. Many studies have also suggested that pathogens can exploit glucose as either a nutrient or a signal molecule that induces virulence functions [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Indeed, glucose acquisition is essential for the full virulence potential of pathogenic bacteria [ 11 , 12 ] including Pseudomonas aeruginosa , a major cause of nosocomial infection as well as infection in hosts with compromised defenses [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose is an essential nutrient for the human body, serving as a primary fuel for energy production [ 1 ]. Many studies have also suggested that pathogens can exploit glucose as either a nutrient or a signal molecule that induces virulence functions [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Indeed, glucose acquisition is essential for the full virulence potential of pathogenic bacteria [ 11 , 12 ] including Pseudomonas aeruginosa , a major cause of nosocomial infection as well as infection in hosts with compromised defenses [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…5c and d ). Since T6P is an inhibitor of Tps1p, and in plants, T6P serves as a signaling molecule ( 3 , 69 , 70 ), we speculate that the T6P level must reach a threshold to inhibit MoTps1 activity. At a persistent threshold level, spontaneous mutation of MoTPS3 is induced (likely via the T6P signaling), which in turn suppresses MoTps1 activity to reduce the level of T6P.…”
Section: Discussionmentioning
confidence: 96%
“…It is a structural component of most organisms, including plants, fungi, lichens, algae, bacteria, insects, and invertebrates, but not vertebrates ( 1 , 2 ). Therefore, disruption of the trehalose biosynthesis pathway could be a promising alternative to developing safe and broad-spectrum fungicidal drugs, especially against human-pathogenic fungi ( 2 , 3 ). To date, five different biosynthesis pathways have been established for the synthesis of trehalose, and the trehalose phosphate synthase/trehalose phosphate phosphatase (TPS/TPP) pathway is the most widely distributed trehalose biosynthesis pathway among these organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Due to clinical limitations of fungicidal agents, high price, inevitable toxicities, and the appearance of drug resistance, the synthesis of effective and safe fungicidal agents based on novel antifungal targets is instantly needed 3 . The key drug molecules which act as inhibitors of β-1,3-glucan biosynthesis have been advocated as potential therapeutic agents for treating fungal infections 4 . It is a glucosyl-transferase enzyme involved in the generation of beta-glucan in fungi which is key component of cell wall construction.…”
Section: Introductionmentioning
confidence: 99%